2018
DOI: 10.1111/ejn.13923
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with the GSK3‐beta inhibitor Tideglusib improves hippocampal development and memory performance in juvenile, but not adult, Cdkl5 knockout mice

Abstract: Cyclin-dependent kinase-like 5 (CDKL5) disorder is a severe neurodevelopmental disorder characterized by early-onset epileptic seizures, severe developmental delay, and intellectual disability. To date, no effective pharmacological treatments are available to improve the neurological phenotype that is due to mutations in the CDKL5 gene. Murine models of CDKL5 disorder have recently been generated, making the preclinical testing of pharmacological interventions possible. Using a Cdkl5 knockout (KO) mouse model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 36 publications
(73 reference statements)
7
42
1
Order By: Relevance
“…Spontaneous synaptic activity is impaired in hippocampal slices of a forebrain excitatory neuron specific to Cdkl5 KO mice [Nex‐cKO; ], and excitatory synaptic transmission is reduced in mouse hippocampal cultures silenced for Cdkl5 . Altered neuronal survival, dendritic development and synaptic function may underlie the severe hippocampus‐dependent cognitive impairment that characterizes Cdkl5 KO mice .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous synaptic activity is impaired in hippocampal slices of a forebrain excitatory neuron specific to Cdkl5 KO mice [Nex‐cKO; ], and excitatory synaptic transmission is reduced in mouse hippocampal cultures silenced for Cdkl5 . Altered neuronal survival, dendritic development and synaptic function may underlie the severe hippocampus‐dependent cognitive impairment that characterizes Cdkl5 KO mice .…”
Section: Introductionmentioning
confidence: 99%
“…CDKL5 forms a complex with PSD‐95 and NGL‐1 at the spine level to regulate spine morphology and maintenance , and with IQ domain‐containing GTPase‐activating protein 1 (IQGAP1) and MAP1S to regulate microtubule dynamics and stability . Although data clearly suggest that CDKL5 is important for correct neuronal maturation , the role of CDKL5 in the maintenance of neuron survival has been poorly investigated. In addition, the mechanisms by which CDKL5 supports neuronal survival remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These studies include the use of NMDA receptor modulators: allopregnanolone (a neurosteroid restoring normal morphology of microtubules); tineptin (an antidepressant affecting AMPA receptors); and insulin-like growth factor IGF-1, activating AKT/mTORY serotonergic receptor agonist 5-HT7R-LP-211 [55,56]. Recently, the results of a study carried out on a CDD-loaded mouse population have been published, which demonstrated the beneficial effect of GSK3β receptor (tideglusib) inhibition on hippocampal development and hippocampus-dependent learning memory in young individuals [57]. The achievements of modern technology also allow the development of methods of protein substitution therapy, which was described by Trazzi [58]; TAT-CDKL5 fusion proteins were used, which, crossing the barrier, reach the CNS while maintaining the CDKL5 protein activity.…”
Section: Therapymentioning
confidence: 99%
“…These defects were accompanied by increased activity of GSK3β, an important inhibitory regulator of many neuronal functions [17]. Therefore, tideglusib was tested on Cdkl5 knockout mice and results showed that tideglusib improved hippocampal development, hippocampus-dependent behaviors, and memory performance in juvenile Cdkl5 knockout mice [24].…”
Section: Cdkl5mentioning
confidence: 99%